Arterial Thrombosis in Patients with Human Immunodeficiency Virus: Two-Case Reports and Review of the Literature - C. Konin; J. B. Anzouan-Kacou; A. Essam N'loo (Case Reports in Vascular Medicine)
Thrombosis during HIV infection was commonly vein thrombosis. Arterial thrombosis is also more and more described. We report two cases detected in the Abidjan Cardiology Institute. Case Reports. Case 1: an HIV infected female presented with sudden loss of consciousness and right hemiplegia. She had been taking HAART regimen for five years. Neck vessels ultrasonography revealed thrombosis on left ICA. Anticoagulant treatment leads to reduction of symptoms and left ICA partial recanalization. Case 2: male HIV infected taking HAART therapy was admitted for an acute pain of left lower limb; examination showed a decrease of heat, sensitivity, and mobility of this limb with popliteal and tibial pulses abolished. Arterial ultrasonography and CT angiography showed occlusion on the lower third of superficial femoral artery and homolateral popliteal artery suggesting a thrombosis of this artery. He underwent a femorotibial bypass surgery and anticoagulant treatment. The outcome was good with reappearance of local heat of the limb and tibial pulses. Probable etiology is early carotid atherosclerosis associated with protein S deficiency in the first case and antiphospholipid syndrome in the second case. Conclusion. Arterial thrombosis might occur in HIV infection. Several etiological factors could be involved in the pathogeny of these arterial thromboses.